2010
DOI: 10.1148/radiol.10091334
|View full text |Cite
|
Sign up to set email alerts
|

Intraindividual Comparison of Gadoxetate Disodium–enhanced MR Imaging and 64-Section Multidetector CT in the Detection of Hepatocellular Carcinoma in Patients with Cirrhosis

Abstract: Compared with multiphasic 64-section multidetector CT, gadoxetate disodium-enhanced MR imaging yields significantly higher diagnostic accuracy and sensitivity in the detection of HCC in patients with cirrhosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
171
0
3

Year Published

2011
2011
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 240 publications
(178 citation statements)
references
References 40 publications
4
171
0
3
Order By: Relevance
“…64,65 Several studies have shown that gadoxetic acid-enhanced MR imaging is useful in diagnosing conventional HCCs and, in fact, may sometimes be more reliable than dynamic contrast-enhanced 16-to 64-slice multidetector-row CT for this purpose. 9,36,66,67 When using an extracellular GBCA, sensitivity and specicity of MR imaging are excellent even for small HCCs. 68 However, some researchers suggest that the hepatocyte phase of gadoxetic acid might have added value to detect more HCCs than dynamic phases especially for less-experienced observers.…”
Section: Added Value For Hepatocellular Carcinoma (Hcc) Improving Diamentioning
confidence: 99%
“…64,65 Several studies have shown that gadoxetic acid-enhanced MR imaging is useful in diagnosing conventional HCCs and, in fact, may sometimes be more reliable than dynamic contrast-enhanced 16-to 64-slice multidetector-row CT for this purpose. 9,36,66,67 When using an extracellular GBCA, sensitivity and specicity of MR imaging are excellent even for small HCCs. 68 However, some researchers suggest that the hepatocyte phase of gadoxetic acid might have added value to detect more HCCs than dynamic phases especially for less-experienced observers.…”
Section: Added Value For Hepatocellular Carcinoma (Hcc) Improving Diamentioning
confidence: 99%
“…Gadoxetate disodium, a recently introduced hepatobiliary contrast agent, is widely used to improve detection and characterization of HCC (17)(18)(19)(20)(21). In clinical practice, we have observed areas of hypointensity around some HCCs on hepatobiliary phase images of gadoxetate disodium-enhanced MRI (EOB-MRI).…”
mentioning
confidence: 99%
“…[13][14][15] Therefore, this technique may more readily detect early-stage lesions than CT arterial portography, 16 which was believed to have the highest sensitivity for this purpose. 9 The increased use of gadoxetic acid for routine examination may lead to the more frequent detection of hypovascular nodules that are hypointense on hepatocyte-phase (15 to 20 min after administration of gadoxetic acid) images of gadoxetic acidenhanced MR imaging.…”
Section: Magnetic Resonance In Medical Sciencesmentioning
confidence: 99%